2009
DOI: 10.1007/s10696-010-9063-2
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of value-added product recovery activities in SMEs using multiple case studies of OEMs and independent remanufacturers

Abstract: This paper presents an empirical study of certain features of the practices and management of value recovery processes that follow the acquisition of used products. The research focuses on the implementation of refurbishing and remanufacturing in small and medium enterprises. Twelve cases have been examined in detail, representing both original equipment manufacturers (OEMs) and independent remanufacturers (IRs), with different products and nature of operations. The analysis indicates that the factors having t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…This research identified that case study is the most used research method on the LSS field in Brazil, and according to Zhang et al (2012); Endler et al (2016); Yadav and Desai (2016) and Raval and Kant (2017), it occurs around the world. The use of the case study is appropriate when a well-developed set of theories are still lacking (Eisenhardt, 1989; Kapetanopoulou and Tagaras, 2009), such as LSS in Brazil. Besides Brazil, the intensive adoption of case study also supports that LSS is in earlier stages of development around the world (Raval and Kant, 2017).…”
Section: Analysis and Discussion Of Reviewed Literaturementioning
confidence: 99%
“…This research identified that case study is the most used research method on the LSS field in Brazil, and according to Zhang et al (2012); Endler et al (2016); Yadav and Desai (2016) and Raval and Kant (2017), it occurs around the world. The use of the case study is appropriate when a well-developed set of theories are still lacking (Eisenhardt, 1989; Kapetanopoulou and Tagaras, 2009), such as LSS in Brazil. Besides Brazil, the intensive adoption of case study also supports that LSS is in earlier stages of development around the world (Raval and Kant, 2017).…”
Section: Analysis and Discussion Of Reviewed Literaturementioning
confidence: 99%
“…In this matter, casebased research was adopted for gathering and analysing field data. It is an appropriate method for theory building, extension or refining in emerging subjects (such as RL), where a well-developed set of theories are scarce (Eisenhardt 1989;Kapetanopoulou and Tagaras 2009).…”
Section: Methodsmentioning
confidence: 99%
“…It is noted that the research presented in this paper is part of a larger empirical study of PRA in the Greek industry. The entire research plan includes a second questionnaire-based survey that will permit the derivation of conclusions regarding developments over time, as well as case research that enables a deeper understanding of more detailed PRA features and practices (Kapetanopoulou and Tagaras, 2009). We must also clarify that our research is descriptive and exploratory in nature rather than confirmatory per the distinction of Forza (2002).…”
Section: Introductionmentioning
confidence: 99%